Reflections on the readings of Sundays and feasts: June-August 2025 - Hart, Sarah L. (The Australasian Catholic record, 2025)
The last verses of the Gospel of Luke and the opening verses of Acts overlap in today's readings. Both texts, written by the same author, give an account of the ascension of Jesus into heaven. The meaning of the word 'ascension', from the Latin verb ascendere, relates to rising or moving upward. In Luke's Gospel, Jesus is described as 'carried up to heaven' and in Acts as 'lifted up', providing us with a vivid image of Jesus being transported upwards in a movement depicting departure, and leaving this earthly world.